FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Dinda Puspitasari, 13.05.52.0045; Nurhayati, Ida (Students Journal of Accounting and Banking, 2018)
The study examines the effect of liquidity, profitability, farm size, growth of company, asset structure, and business risk on capital structure. This research on manufacturing company on the Indonesian Stock Exchange by using a go public. The sampling method used purposive sampling with periode from 2014 to 2016. The data are processed as many 232 companies. The thechnique of data testing using multiple linear regression analysis. The result of research shows that Profitability, Company Size, Asset Growth, Business Risk has no effect on capital structure, Liquidity has negative effect to capital structure, Asset Structure has positive effect to capital structure.Keyword: liquidity, profitability, farm size, growth of company, asset structure, and business risk